Analisis determinan tingkat suku bunga dan di Indonesia Tahun 1990-2020 (Pendekatan Error Corection Model) - Erwin , Geiskha; Tan, Syamsurijal; Hodijah, Siti (Jurnal Paradigma Ekonomika, 2023)
This study aims to analyze the development of interest rates, exchange rates, economic growth and government spending in Indonesia in 1990-2020. To analyze the effect of Exchange Rates, Economic Growth, and Government Expenditures on Interest Rates in Indonesia in 1990-2020. The data used in this study is secondary data which was analyzed using the Eviews tool, with the Error Correction Model analysis method. During the period 1990-2020. Based on the results of testing interest rates in Indonesia during the period 1990-2020 using the ECM method, the results show that simultaneously in the long and short term, the variables of Exchange, PE, and Government Expenditures have a significant effect on Interest Rates. Meanwhile, based on the partial test results in the long term, economic growth has a significant effect on interest rates in Indonesia. The exchange rate variable partially in the long term and short term has a significant effect on interest rates, while the Indonesian government's spending in the long term period 1990-2020 has a significant effect, and the short term is not significant.